2008
DOI: 10.1016/j.pain.2008.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid and serotonergic systems are needed for acetaminophen-induced analgesia

Abstract: Acetaminophen is the most used analgesic/antipyretic drug. Its unclear mechanism of action could rely on cyclooxygenase inhibition, NO synthesis blockade or reinforcement of the serotonergic system. Here we show that in thermal, mechanical and chemical pain tests, AM-251, a specific CB(1) receptor antagonist, abolished the analgesic action of acetaminophen, which was also lost in CB(1) receptor knockout mice. Moreover, acetaminophen was shown unable to bind to CB(1) receptors demonstrating an indirect involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
168
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(188 citation statements)
references
References 48 publications
13
168
0
2
Order By: Relevance
“…Involvement of this receptor in the action of paracetamol was confirmed by a study showing that CB 1 knockout mice and rats pretreated with a specific CB 1 antagonist (AM251) were insensitive to paracetamol [5,28]. Corroborating these results, we showed that the analgesic effect of p-aminophenol was also suppressed by AM251 [6].…”
Section: Cb 1 Receptorsupporting
confidence: 73%
See 3 more Smart Citations
“…Involvement of this receptor in the action of paracetamol was confirmed by a study showing that CB 1 knockout mice and rats pretreated with a specific CB 1 antagonist (AM251) were insensitive to paracetamol [5,28]. Corroborating these results, we showed that the analgesic effect of p-aminophenol was also suppressed by AM251 [6].…”
Section: Cb 1 Receptorsupporting
confidence: 73%
“…Both strategies resulted in the abolition of paracetamol-induced (1) brain synthesis of AM404 and (2) analgesic action [5]. Likewise, the analgesic effect and brain formation of AM404 induced by p-aminophenol were decreased in FAAH −/− mice and in rats pretreated with PMSF [6].…”
Section: Paracetamol a Prodrug Of Which Am404 Is The Active Metabolitementioning
confidence: 97%
See 2 more Smart Citations
“…Paracetamol acts mainly on the brain and spinal cord; nevertheless, the exact mechanism of action has not been fully elucidated. [4] The prostaglandin H 2 synthase (PGHS), [5] the serotoninergic system, [6,7] and/or the cannabinoid system [8,9] have been proposed as potential targets. The action of NSAIDs mainly relies on the inhibition of prostaglandin biosynthesis at the site of the inflammation, [10] although some NSAIDs also exhibit a central action.…”
Section: Introductionmentioning
confidence: 99%